2001
DOI: 10.1037/0882-7974.16.3.427
|View full text |Cite
|
Sign up to set email alerts
|

Latent growth models of the longitudinal effects of dementia caregiving: A comparison of African American and White family caregivers.

Abstract: Self-report measures of depression, physical health symptoms, and life satisfaction were collected over a 2-year period from 197 family caregivers of dementia patients and 218 noncaregivers (controls). Latent growth models were used to compare changes across time for African American and White caregivers, with gender, age, and socioeconomic status serving as covariates. Results indicated that White caregivers sustained higher levels of elevated depression and decreasing life satisfaction over time compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
84
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 119 publications
(91 citation statements)
references
References 42 publications
7
84
0
Order By: Relevance
“…However, resilience was both a positive association and a moderating factor, attenuating the symptoms of depression among black caregivers. 19 Similar results were reported by Clay et al, 20 who spent five years monitoring a sample of 166 American caregivers (mean age of 60 years) who cared for individuals that had been classified with dementia. The aim of the study was to analyze their satisfaction with social support and depression symptoms, thereby confirming the resilience found among white and black caregivers.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…However, resilience was both a positive association and a moderating factor, attenuating the symptoms of depression among black caregivers. 19 Similar results were reported by Clay et al, 20 who spent five years monitoring a sample of 166 American caregivers (mean age of 60 years) who cared for individuals that had been classified with dementia. The aim of the study was to analyze their satisfaction with social support and depression symptoms, thereby confirming the resilience found among white and black caregivers.…”
Section: Discussionsupporting
confidence: 75%
“…Roth et al 19 spent two years monitoring 197 family caregivers of people with dementia and 218 non-caregivers, assessing depression, physical health and satisfaction. The authors sought to identify differences between white and black caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Haley and colleagues showed that these appraisal differences were partly responsible for explaining observed racial differences on measures of depression and life satisfaction. Taken together, the present findings add to a larger body of evidence that suggests African American family caregivers are less susceptible to the emotional distress associated with dementia caregiving than are White family caregivers (Connell & Gibson, 1997;Roth et al, 2001). Additional research is needed to more fully describe and explain the relative advantages that African American family caregivers consistently report in comparison with White caregivers on measures of emotional distress and caregiving burden.…”
Section: Discussionmentioning
confidence: 75%
“…Caregivers as a group have been found to report deteriorating physical health over time compared with noncaregivers (Roth et al, 2001), and caregivers who report being burdened by their responsibilities have been shown to have increased mortality rates (Schulz & Beach, 1999). Consequently, it is important to routinely assess the amount of ongoing memory and behavior problems that persons with dementia are displaying and the degree to which these problems are distressing to the family members who care for them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation